FAKTOR PENYEBAB KEMISKINAN NELAYAN DI KELURAHAN PURUS KECAMATAN PADANG BARAT (Jurnal Pelangi : Research of Education and Development, 2011)
The causing factors of the poverty of the fishermen in Purus village are (1) naturalfactors which is caused by the unsupportive natural condition used for business outsidethe beach, and the have physical limitation because of sick, so that they are not optimumin cultivating the available resources, (2) Cultural factors which indicates that almost allof the Purus village people are used to the lazy culture and the attitude of let-it-be, andunwilling of change their destiny to a better one because the education of the people inPurus village is under achieved, so that they only focus on fishing business, (3) structuralfactors indicates that Purus society do not have any effort to change their destiny, inwhich this is caused by complicated system policy of bureaucracy institution, such as theunavailability of better fishing tools.